2021
DOI: 10.1101/2021.02.10.430677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential roles of RIG-I-like receptors in SARS-CoV-2 infection

Abstract: The retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated protein 5 (MDA5) are the major viral RNA sensors that are essential for activation of antiviral immune responses. However, their roles in severe acute respiratory syndrome (SARS)-causing coronavirus (CoV) infection are largely unknown. Herein we investigate their functions in human epithelial cells, the primary and initial target of SARS-CoV-2, and the first line of host defense. A deficiency in MDA5 (MDA5-/-), RIG-I or mitoch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The induction of cytokine production in MNPs in COVID-19 can either be triggered via recognition of damage-associated molecular patterns (DAMPS) released from epithelial cells affected by SARS-CoV-2 by PRRs or by direct recognition of viral pathogen-associated molecular patterns (PAMPs) via specific Toll-like receptors, i.e. TLR2 and TLR4, the retinoic acid-inducible gene I (RIG-I) or the melanoma differentiation associated gene (MDA)-5 (116)(117)(118)(119). Furthermore, C-type lectin receptors, including DC-SIGN, L-SIGN, LSECtin, ASGR1, CLEC4K (Langerin) and CLEC10A (MGL), as well as Tweety family member 2 have been identified to interact with the SARS-CoV-2 spike protein inducing proinflammatory responses, but not allowing direct infection.…”
Section: The Role Of Monocytes and Alveolar Macrophages In Covid-19mentioning
confidence: 99%
“…The induction of cytokine production in MNPs in COVID-19 can either be triggered via recognition of damage-associated molecular patterns (DAMPS) released from epithelial cells affected by SARS-CoV-2 by PRRs or by direct recognition of viral pathogen-associated molecular patterns (PAMPs) via specific Toll-like receptors, i.e. TLR2 and TLR4, the retinoic acid-inducible gene I (RIG-I) or the melanoma differentiation associated gene (MDA)-5 (116)(117)(118)(119). Furthermore, C-type lectin receptors, including DC-SIGN, L-SIGN, LSECtin, ASGR1, CLEC4K (Langerin) and CLEC10A (MGL), as well as Tweety family member 2 have been identified to interact with the SARS-CoV-2 spike protein inducing proinflammatory responses, but not allowing direct infection.…”
Section: The Role Of Monocytes and Alveolar Macrophages In Covid-19mentioning
confidence: 99%
“…Indeed, DCs are equipped with a wide arsenal of PRRs responsible for the detection of several viral components. Among the PRRs involved in SARS-CoV-2 sensing are TLR7 [59], RIG-I [60], MDA5 [61] and possibly cGAS-STING [62]. Upon binding to their agonists, PRRs initiate a signaling pathway which culminates in the activation of IRF3, IRF7 and NF-κB.…”
Section: Sars-cov-2: Mechanisms Of Recognition and Early Immune Responsementioning
confidence: 99%
“…Studies have shown that SARS-CoV-2 RNA could trigger activation of the RIG-I-MAVS pathway and enhance the release of type-I IFN [ 129 ]. Yang et al [ 130 ] found that after knocking out RIG-I, MDA5, or mitochondrial antiviral-signaling protein (MAVS), SARS-CoV-2-infected human endothelial cells produced notably less type-I/III IFN and the expression of ACE2 was increased. In alveolar epithelial cells, ORF9B inhibited the release of IFN, thereby inhibiting antiviral immunity [ 129 ].…”
Section: Ace2 Sars-cov-2 and Innate Immune Pathwaysmentioning
confidence: 99%